Bowel obstruction and perforation secondary to progressive heterotopic mesenteric ossificans - Emily M. Louis; Savvas Nicolaou, MD (Radiology Case Reports, 2022)
Heterotopic mesenteric ossification (HMO) is a rare condition which usually affects male patients. Its defining feature is hyperdense ossification in the mesentery, usually following surgery or trauma. Due to potentially serious complications that can arise from HMO, it is essential to recognize it in its nascent stages. In this case study, a 65-year-old male was imaged by CT scan serially over several years for recurrent bowel obstruction as a result of worsening HMO, providing new insight into the natural progression of this condition. Mechanical injury of the bowel eventually caused perforation and abscess formation.